2010
DOI: 10.1111/j.1365-2982.2010.01619.x
|View full text |Cite
|
Sign up to set email alerts
|

A bi-directional assessment of the human brain-anorectal axis

Abstract: Background/Aim Brain-gut dysfunction has been implicated in gastrointestinal disorders but a comprehensive test of brain-gut axis is lacking. We developed and tested a novel method for assessing both afferent anorectal-brain function using cortical evoked potentials (CEP), and efferent brain-anorectal function using motor evoked potentials (MEP). Methods CEP was assessed following electrical stimulations of anus and rectum with bipolar electrodes in 26 healthy subjects. Anorectal MEPs were recorded following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 41 publications
(160 reference statements)
2
52
0
Order By: Relevance
“…Previously, EPs have been established in healthy control studies to be effective in measuring the integrity of the afferent nerve supply to the bowel, providing robust and temporally reproducible data. 15,18,19,42 In the current study, traces were obtained with similar morphologies to those recorded in prior studies, 15,42 with latencies at N1 and P2 within the ranges previously reported in healthy volunteers, although the amplitude of each peak was somewhat reduced. This may be a consequence of pain threshold, rather than maximal tolerated sensation being used to evoke the cortical potentials in this study.…”
Section: Comparison With Previous Studiessupporting
confidence: 83%
See 1 more Smart Citation
“…Previously, EPs have been established in healthy control studies to be effective in measuring the integrity of the afferent nerve supply to the bowel, providing robust and temporally reproducible data. 15,18,19,42 In the current study, traces were obtained with similar morphologies to those recorded in prior studies, 15,42 with latencies at N1 and P2 within the ranges previously reported in healthy volunteers, although the amplitude of each peak was somewhat reduced. This may be a consequence of pain threshold, rather than maximal tolerated sensation being used to evoke the cortical potentials in this study.…”
Section: Comparison With Previous Studiessupporting
confidence: 83%
“…Somatosensory evoked potentials are a widely used neurophysiological tool to investigate afferent neuronal function 14,15 ; however, the use of visceral evoked potentials in clinical research is still evolving. The technique has been assessed extensively in healthy volunteer studies, [15][16][17][18][19] and more recently used to demonstrate changes in afferent neuronal function in patients with visceral hypersensitivity and irritable bowel syndrome 20,21 and also in childhood chronic constipation. 22,23 In addition to yielding information regarding conduction velocity and response amplitude, spatial localization of brain generators (dipole sources) can be extrapolated via analysis using ''inverse modeling'' of recorded data.…”
Section: Conclusion and Inferencesmentioning
confidence: 99%
“…Depending on the site of stimulation and recording, afferent and efferent pathways can be evaluated 59, 60 . Confirming proof of concept, motor evoked potentials after anal and rectal stimulation were prolonged in patients with spinal cord injury and bowel dysfunction 61 and also in FI 62 .…”
Section: Fecal Incontinencementioning
confidence: 99%
“…Bi-directional assessment of BGA has been recently described using CEPs and MEPs in healthy humans (69). Using this approach it is possible to assess the afferent and efferent pathways in the same subject thereby providing a good temporal and spatial resolution.…”
Section: Bidirectional Pathways In Bgamentioning
confidence: 99%